Characteristics Analysis of Joint Acoustic Echo and Noise Suppression in Periodic Drillstring Waveguide - Li Cheng; Chang Jinfeng; Liu Zhao; Fan Shangchun; Ding Tianhuai (Shock and Vibration)
A new method of wireless data telemetry used by oil industry uses compressional acoustic waves to transmit downhole information from the bottom hole to the surface. Unfortunately, acoustic echoes and drilling vibration noises in periodic drillstring are a major issue in transmission performance. A combined acoustic echo and noise suppression method based on wave motion characteristic in drillstring is adopted to enhance an upward-going transmitted acoustic signal. The presented scheme consists of a primary acoustic echo canceller using an array of two accelerometers for dealing with the downward-going noises and a secondary acoustic insulation structure for restraining the upward-going vibration noises. Furthermore, the secondary acoustic insulation structure exhibits a banded and dispersive spectral structure because of periodic groove configuration. By using a finite-differential algorithm for the one-dimensional propagation of longitudinal waves, acoustic receiving characteristics of transmitted signals are simulated with additive Gaussian noise in a periodic pipe structure of limited length to investigate the effects on transmission performance optimization. The results reveal that the proposed scheme can achieve a much lower error bit ratio over a specified acoustic isolation frequency range with a 30–40 dB reduction in the average noise level compared to traditional single-receiver scheme.